Peroxin FgPEX22-Like Is Involved in FgPEX4 Tethering and Fusarium graminearum Pathogenicity - Zhang, Li; Liu, Chunjie; Wang, Mingyu; Tao, Yilin; Liang, Yuancun; Yu, Jinfeng (Frontiers in Microbiology, 2021)
Peroxisomes are essential organelles that play important roles in a variety of biological processes in eukaryotic cells. To understand the synthesis of peroxisomes comprehensively, we identified the gene FgPEX22-like, encoding FgPEX22-like, a peroxin, in Fusarium graminearum. Our results showed that although FgPEX22-like was notably different from other peroxins (PEX) in Saccharomyces cerevisiae, it contained a predicted PEX4-binding site and interacted with FgPEX4 as a rivet protein of FgPEX4. To functionally characterize the roles of FgPEX22-like in F. graminearum, we performed homologous recombination to construct a deletion mutant (ΔPEX22-like). Analysis of the mutant showed that FgPEX22-like was essential for sexual and asexual reproduction, fatty acid utilization, pathogenicity, and production of the mycotoxin deoxynivalenol. Deletion of FgPEX22-like also led to increased production of lipid droplets and decreased elimination of reactive oxygen species. In addition, FgPEX22-like was required for the biogenesis of Woronin bodies. Taken together, our data demonstrate that FgPEX22-like is a peroxin in F. graminearum that interacts with PEX4 by anchoring PEX4 at the peroxisomal membrane and contributes to the peroxisome function in F. graminearum.